PENGARUH STRUKTUR MODAL, BIAYA OPERASIONAL, DAN PROFITABILITAS TERHADAP PPH BADAN - Wulan; Linawati; Kurniawan, Andy (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2024)
Corporate income tax is important for a company as credibility also shows that the company is in good condition. Several things influence the amount of corporate income tax, including capital structure, operational costs, and profitability. This research aims to measure the influence of capital structure, operational costs, and profitability on corporate income tax. Using a purposive sampling technique, the sample used was 76 financial reports from 19 food and beverage companies listed on the IDX for 2020-2023. This research uses a quantitative approach to causality with multiple linear regression analysis. To fulfill the analysis requirements, classical assumption tests were carried out (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test). Research results: (1) Capital Structure partially has no significant effect on corporate Income Tax, (2) Operational Costs and profitability partially have a significant effect on corporate Income Tax, and (3) Capital Structure, Operational Costs, and Profitability simultaneously have a significant effect on corporate income tax.